Analysis of the Effect of Linear and Non Linear Loads on the Effectiveness of Single Phase Transformers - Sudibya, Bambang; Irawaty, Mardiana (Institut Teknologi Dirgantara Adisutjipto, 2018)
Lately, PLN as the state electricity company that supplmost of the electricity needs in Indonesia is being hit by a